Critical Role of Innate Immunity to Flagellin in the Absence of Adaptive Immunity. (24th August 2020) - Zou, Jun; Zhao, Xu; Shi, Zhenda; Zhang, Zhan; Vijay-Kumar, Matam; Chassaing, Benoit; Gewirtz, Andrew T
Abstract: Background: Bacterial flagellin is a major target of innate and adaptive immunity, both of which can promote and/or compensate for deficiencies in each other's function. Methods: To investigate the role of innate immune detection of flagellin irrespective of adaptive immunity, we examined the consequences of loss of Toll-like receptor 5 (T5) and/or Nod-like receptor 4 (N4) upon a Rag1-deficient background. Results: Mice lacking Toll-like receptor 5 and Rag1 (T5/Rag-DKO) exhibited frequent lethal Pasteurellaceae-containing abscesses that prevented breeding of these mice. Mice lacking Toll-like receptor 5, Nod-like receptor 4, and Rag1 (T5/N4/Rag-TKO) also resulted in sporadic lethal abdominal abscesses caused by similar Pasteurellaceae. In the absence of such infections, relative to Rag1-KO, T5/N4/Rag-TKO mice exhibited microbiota encroachment, low-grade inflammation, microbiota dysbiosis, and, moreover were highly prone to Citrobacter infection and developed severe colitis when adoptively transferred with colitogenic T cells. Relative proneness of T5/N4/Rag-TKO mice to T-cell colitis was ablated by antibiotics while fecal microbiota transplant from T5/N4/Rag-TKO mice to wild-type mice transferred proneness to Citrobacter infection, indicating that dysbiosis in T5/N4/Rag-TKO mice contributed to these phenotypes. Conclusions: These results demonstrate a critical role for innate immune detection of flagellin, especially in the intestinal tract and particularly in hosts deficient in adaptive immunity. Abstract : This study showed that, in the absence of adaptive immunity, mice deficient in innate immunity to flagellin developed microbiota dysbiosis and occasional lethal Pasteurellaceae infections. Moreover, such mice were highly prone to pathogen infection and T-cell–induced colitis.